(untitled) (Scientific journal of the Fergana State University, 2025)
This article discusses the scientific heritage and philosophical teachings of our great thinkers, which speak about relations in social life, the relationship between state and religion, and how they were able to create their own Eastern concepts of tolerance and tolerance. The main essence of the concepts of Eastern thinkers on the principles of tolerance and interethnic good-neighborliness is interpreted in direct connection with the spiritual and mental state of a person.